Reconstruction of 3D Models of Fishing Boat Propellers Using Photogrammetry and Reverse Engineering Techniques - Van, Tuong Nguyen; Naprstkova, Natasa (Manufacturing Technology Journal, 2024)
The conventional method for measuring propeller geometric parameters involves utilizing specialized equipment or 3D measuring devices. Currently, specific propeller geometry parameters can be as-sessed by employing virtual measurements performed on a virtual propeller model generated using reverse engineering methods. This paper introduces a novel approach to constructing 3D models of small fishing boat propellers using photogrammetry and reverse engineering techniques. In this method, the propeller is captured through photographs taken with a smartphone camera employing special techniques. Subsequently, these images are processed using Agisoft Metashape to generate a mesh model, from which a precise photogrammetric model of the propeller is developed using CATIA. By comparing the photogrammetric model with the scanned model in GOM Inspect, and evaluating the measurement outcomes of blade radius and pitch on virtual and physical models, it is possible to ascertain that the photogrammetric model exhibits exceptional accuracy. Consequently, the photogrammetric model can be effectively utilized for the measurement of propeller geometric parameters.
Keywords: Photogrammetry; Reverse Engineering; Smartphone; Fishing boat; Propeller